Selenium Increases Ureide Metabolism and Yield of Cowpea Plants: Examining Se Distribution in Leaves and Seeds Using Microprobe X-Ray Fluorescence Spectroscopy - Mendes, Nandhara Angélica Carvalho [UNESP]; Lanza, Maria Gabriela Dantas Bereta [UNESP]; Silva, Vinícius Martins [UNESP]; Bosse, Marco Antonio [UNESP]; Montanha, Gabriel Sgarbiero; de Carvalho, Hudson Wallace Pereira; Cunha, Matheus Luís Oliveira [UNESP]; dos Reis, André Rodrigues [UNESP] (Springer Nature, 2023)
Selenium (Se) is considered beneficial to plants at low concentrations because of its role in boosting antioxidant metabolism. The range between benefit and toxicity of Se is narrow for living beings. Since Se deficiency is observed in soils worldwide, dose–response studies are needed to define critical doses of Se toxicity for different plant species. This study aimed to characterize the dose response of Se in cowpea plants by evaluating ureide metabolism, ultrastructural responses, and Se distribution in leaf and seed tissues. Selenium concentration in leaves and seeds increased linearly in response to sodium selenite application. Cowpea yield increased by 40% in response to 50 g Se ha−1. Selenium application also linearly increased the ureide and nitrate concentrations in cowpea leaves. The concentrations of allantoic acid and free amino acids increased up to 200 g Se ha−1. The increase in ureides up to 200 g Se ha−1 is attributed to increments of biologically fixed nitrogen in cowpea plants. From that dose on, the increase in ureides is related to the antioxidant capacity. Above 50 g ha−1, Se application induced chlorosis on the leaf blade by promoting coalescence of the brown-colored lesions. Microprobe X‑ray fluorescence spectroscopy revealed higher Se count rates in necrotic regions of leaf tissue, confirming the toxicity of Se. Additionally, increased Ca intensity was also recorded in the region with the highest Se intensity; hence, Ca might play a role in attenuating the stress caused by Se. Selenium was found throughout all seed regions, especially in the embryo.
Keywords: Calcium; Nitrate; Toxicity; Vigna unguiculata; X‑ray fluorescence spectroscopy